Досвід ліберального реформування української економіки (1991–2005 рр.) - Біла, С.О. (Український історичний журнал, 2006)
У контексті історико-економічних досліджень висвітлюються особливості етапів лібералізації економіки України за період 1991–2005 рр. Показано наслідки впровадження «шокової» моделі реформування, визначено об'єктивні передумови переходу до розбудови в нашій державі змішаної економіки. Детально досліджено основні положення програм українського уряду щодо реформування національної економіки, дається їх оцінка з позицій соціально-економічної ефективності. In the context of historical and economical research the peculiarities of the stages of liberalization of economics of Ukraine for the period from 1991 to 2005 are displayed. The consequences of introduction of «shock» model of reforming are shown, the objective initial conditions of change to developing mixed economics in Ukraine are defined. The main points of the programs of Ukrainian parliament concerning the reforming of national economics are examined in details, their appraisal is given from the positions of socio-economical effectiveness.